The Influence of Work Culture, Human Resource Management Practices, Communication, and Compensation on the Performance of Private Vocational High School Employees - Nani Sudiarti; Tri Widyaastuti; I Nyoman Sawitri; Zahara Tussoleha Rony (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The Influence of Work Culture, Human Resource Management Practices, Communication, and Compensation on the Performance of Private Vocational High School Employees